Study of Antioxidant Properties and DNA Interaction of Some Novel 4,5-Dihydro-1H-1,2,4-triazol-5-one Derivatives - Arslantas, Ali; Yuksek, Haydar; Gusoy-Kol, Ozlem; Ocak, Zafer; Tomruk, Zeynep; Calapoglu, Mustafa (Asian Journal of Chemistry, 2012)
3-Alkyl(aryl)-4-amino-4,5-dihydro-1H-1,2,4-triazol-5-ones (2) reacted with 4-benzenesulfonyloxybenzaldehyde (3) to afford the corresponding seven novel 3-alkyl(aryl)- 4-(4-benzenesulfonyloxybenzylidenamino)-4,5-dihydro-1H-1,2,4-triazol-5-ones (4). The acetylation reactions of compounds 4 were investigated and 5 type compounds were obtained. The 14 new compounds synthesized were characterized by using IR, 1H NMR, 13C NMR and UV spectral data together with elemental analysis. The synthesized compounds were analyzed for their in vitro potential antioxidant activities in three different methods. Those antioxidant activities were compared to standard antioxidants such as BHA, BHT and a-tocopherol. In addition, the interaction of the synthesized compounds 4 with cat DNA was investigated by using electrophoresis measurements. Results suggest that the compounds do not interact with the DNA. Furthermore, to investigate the effects of solvents and molecular structure upon acidity, compounds 4 were titrated potentiometrically with tetrabutylammonium hydroxide in five non-aqueous solvents (isopropyl alcohol, tert-butyl alcohol, N,N-dimethylformamide, acetone and dimethyl sulphoxide). The half-neutralization potential values and the corresponding pKa values were determined for all cases.